Political Theory and Social Science - Gunnell, J. author. aut Link
X, 189 p.
Keywords: This work is devoted to a critical analytical examination of the history, character, and conduct of contemporary academic political theory and to a reconsideration of significant elements of this field of inquiry from the perspective of the philosophy of Ludwig Wittgenstein.